Education's impact on social mobility: Mediating parental and child class in Indonesia - Arfines, Fuska Atomita Restu; Pitoyo, Agus Joko; Susilastuti, Dewi Haryani; Pangaribowo, Evita Hanie (Publisher of Widyagama University of Malang (UWG Press), 2024)
The interplay between occupational class, social status, and education in Indonesia is shaped by multiple forces, including economic changes, traditional social structures, and the growing significance of education in determining social mobility. This research aims to address the role of education and family background on child’s class measured by occupational status. This included measuring the relationship between parents’ education and parent’s occupational class as the family background determinant. The main data used to test the model was secondary data from the Indonesian Family Life Survey wave 1 to 4, allowing us to analyze the social class of father and child pairs, as the subject of this study, with a sample size of 4,035. Through path analysis, the finding shows the indirect pathway, mediated through education, displays a greater influence than the direct pathway. This suggests that education plays a critical role as a mediator in determining occupational status and social mobility. This finding is key to understand the persistent inequities in educational access in Indonesia, where family background continues to have a strong effect on children's educational and occupational outcomes. It suggests that policy interventions targeting educational equity could significantly reduce the impact of family background and promote social mobility. JEL Classification: F68; I25; Z13